Application of Mesh-free Methods in Transient Dynamic Analysis of Orthotropic Plates - Soukup, Josef; Zmindak, Milan; Skocilas, Jan; Rychlikova, Lenka (Manufacturing Technology Journal, 2014)
The requirements for reducing the weight and increasing the strength and carrying capacity of the plane and space structures are constantly growing. The one of the way how to meet demands is to use the layered shell composite structures. They could be applied not only in mechanical engineering (containers, pressure vessels, etc.) but also in the civil engineering (cooling towers, roofs, etc.). The article deals with computation procedure of shell and plates using meshless methods. A mesh-free local Petrov-Galerkin (MLPG) method is applied to solve laminate plate problems described by the Reissner-Mindlin theory. Two projection methods are developed to generate the shell surface using the Lagrangian mesh-free interpolations. The bending moment and the shear force expressions are obtained by integration through the laminated plate for the considered constitutive equations in each lamina. The Reissner-Mindlin theory reduces the original three-dimensional (3-D) thick plate problem to a two-dimensional (2-D) problem. Results of transient dynamic loads in the composite plates using MLPG solution are presented here.
Keywords: Composite Materials; Mesh-free Methods; Transient Dynamics; Orthotropic Plates